2015
DOI: 10.1177/0194599814568284
|View full text |Cite
|
Sign up to set email alerts
|

Maxillomandibular Advancement and Tracheostomy for Morbidly Obese Obstructive Sleep Apnea

Abstract: Data for MMA and tracheostomy as treatment for morbidly obese, adult OSA patients are significantly limited. We caution surgeons about drawing definitive conclusions from these limited studies; higher level studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 141 publications
0
13
0
1
Order By: Relevance
“…There are over 28 surgeries described for obstructive sleep apnea (OSA) in adults . The success and cure rates for sleep surgeries can be variable; therefore, to improve outcomes, the surgeries are tailored to individual patients based on their facial skeletal anatomy, nasal anatomy (including turbinate size and septal deviations), tonsil size, tongue size, palate position, and body mass index (BMI) . Tonsillectomy is not mentioned as an option as an isolated surgery to treat adult OSA in the American Academy of Sleep Medicine (AASM) practice guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…There are over 28 surgeries described for obstructive sleep apnea (OSA) in adults . The success and cure rates for sleep surgeries can be variable; therefore, to improve outcomes, the surgeries are tailored to individual patients based on their facial skeletal anatomy, nasal anatomy (including turbinate size and septal deviations), tonsil size, tongue size, palate position, and body mass index (BMI) . Tonsillectomy is not mentioned as an option as an isolated surgery to treat adult OSA in the American Academy of Sleep Medicine (AASM) practice guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise oral appliances are safe, and effective but no cost-effectiveness estimates are available beyond that of the device itself 66 . The most expensive surgical option is mandibular-maxillary advancement but this like tracheostomy is a down-the-line therapy; while it is considered a cure, there is no rigorous objective assessments of cost-effectiveness 67 . What HNS has done is to create another option in OSA management for the CPAP intolerant patient, identify individual factors in determining surgical success, focus definitions of upper airway function, and reenergize surgical interest in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies discussed mini tracheostomies as a subcategory for tracheostomy technique used for the treatment of OSA. A large percentage of the patients who use tracheostomies as treatment for OSA are obese or morbidly obese [16]. Because of the neck adiposity, many studies have demonstrated that obese OSA patients may have persistent obstruction despite having a tracheostomy tube in place [16].…”
Section: Resultsmentioning
confidence: 99%
“…Recent meta-analyses have demonstrated that tracheostomies are effective for treating OSA [15], even in morbidly obese patients [16]. Both tubed and tubeless (permanent) tracheostomies are used as treatment for OSA [17].…”
Section: Introductionmentioning
confidence: 99%